74.3k views
0 votes
The equation 3x^2-6x=8 is rewritten in a form of 3(x-p)^2+q=0.

1 Answer

4 votes

Answer:


3(x - 1)^2 - 11= 0

Explanation:

Given


3x^2 - 6x = 8

Required

Rewrite in form of
3(x - p)^2 + q = 0


3x^2 - 6x = 8

Subtract 8 from both sides


3x^2 - 6x - 8 = 8 - 8


3x^2 - 6x - 8 = 0

Express -8 as 3 - 11;

So, we have:


3x^2 - 6x + 3 - 11= 0

Expand
3x^2 - 6x + 3


3(x^2 - 2x + 1) - 11= 0

Factorize the expression in the bracket;


3(x^2 - x -x + 1) - 11= 0


3(x(x - 1) -1(x - 1)) - 11= 0


3((x - 1)^2) - 11= 0


3(x - 1)^2 - 11= 0

By comparison:
3(x - p)^2 + q = 0


p= 1


q = -11

User The Bassman
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.